Application of software for estabilishing educational comics in pre-service biology teachers education - Asenova, Asya (Yearbook Telecommunications, 2018)
This article presents the pedagogical potential of comics as an educational tool, and the results from a project with pre-service biology teacher in this context. The purpose of this study is to determine the change in students’ attitudes and their motivation towards the integration of educational comics in the field of biological education (as creators and users of educational comics).